Past, current and potential resources of carbon and above-ground plant biomass in the landscape with heaths in some selected areas of the Tuchola Forest - Jarzębski, Marcin; Nienartowicz, Andrzej; Deptuła, Miłosz; Bubnicki, Jakub W.; Domin, Dominik J. (Ecological Questions, 2010)
Applying the GIS technologies, historical and contemporary cartographic materials, data coming from the forest inventory and indices of biomass state, the total biomass and biomass for individual layers of forest and non-forest phytocoenoses, the real and potential biomass was assessed, as well as current and potential carbon resources in that biomass in four nature objects. The investigated objects were characterized by different spatial size, as well as by different intensity of human economic activities and different status of nature conservation. Those were: the Tuchola Forest National Park, the Zaborski Landscape Park, as well as the areas of the so-called (forest) demesne of Zabory and the (field) demesne of Tuchola in the former District (Starosty) of Tuchola. In the case of both demesnes, the biomass state was assessed, as well as the extent of its displacement caused by economic human activities, both nowadays and in the past, i.e. for the year 1796 and 2008. The smallest difference in the state of potential and actual biomass was recorded in the National Park. The loss here amounted to 28.44%. The biggest differences occurred in the field demesne in 1796. The loss here reached 76.47%. It was also observed that nowadays the loss slightly decreased, reaching the level of 73.97%. In the demesne of Zabory, the increase of biomass state was considerably higher during the discussed period. In 1796, when heaths and poor xerothermic meadows covered relatively large areas and were exploited as sheep’s grazing lands, the biomass loss amounted here to 69.32% and in 2008 to 51.87%. The increase of biomass state and at the same time the reduction in biomass losses, calculated in relation to the potential, was brought here about mainly by establishing the Prussian Forest Inspectorate Zwangshof in 1890 and by afforestation of agricultural and fallow lands, which was done by Polish forest inspectorates in the 20th century, particularly during several years after the 2nd World War.